STRATEGI PERMODALAN PEDANGAN PASAR SOPONYONO DI KECAMATAN RUNGKUT KOTA SURABAYA - Eka Fajarwati (JURNAL MANAJERIAL, 2017)
The market is generally divided into two, namely traditional markets and modern markets. Traditional market is a market that has a simple buying and selling activities, there is a bargain with a means of payment in the form of cash. In addition, the market is not only a place for the community in meeting the daily needs, but also the center of the community's economic drive. Traditional market is an important channel in the distribution process of agribusiness products as big as food product of daily necessities. The competition of traditional markets and modern markets is getting tighter. The government is trying to assist the development of traditional markets in order to compete with modern markets by planning the revitalization and fostering of market management so that not only physical improvements are made but also services and market management mangement. Related to this problem is capital strategy applied by traditional market trader Soponyono in face of tight competition with modern market. This research method is descriptive study by using qualitative approach. Data collection techniques through (1) indepth interview, in-depth interviews until the data obtained is considered sufficient and (2) observation that is observing the learning process undertaken. The process of data analysis using capital strategy theory. The selection of this theory is based on the object of research that is Soponyono Surabaya Market so that it can know more deeply about the capital process of Soponyono market traders related to the problem of competition with modern market Based on the result of research known that capital strategy of traditional traders in facing modern market through banking funding, Private capital and BKM and BMT. Obstacles from the cooperation of management of Taman Remaja Surabaya by City Government